1995
DOI: 10.1002/cber.19951281208
|View full text |Cite
|
Sign up to set email alerts
|

The 13C Chemical Shift of the ipso Carbon Atom in Phenyllithium

Abstract: Phenyllithium was labeled with 6Li and I3C at the ipso carbon atom, and the tetramer was measured by solid-state NMR. The chemical shift tensor data were obtained by a moment analysis of the spinning side bands and were compared with the results obtained by calculations with the IGLO method. Although no splitting by dipolar spin coupling to 6Li was found the very good agreement between IGLO predictions and experimental results allowed alignment of the tensor axis to the molecular frame and interpretation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…The σ 11 trends are associated with the σ C1–C NLMOs, while the variations in σ 22 are associated with the σ C1–H NLMO. (Sometimes, a shielding analysis in terms of CMOs can also be very insightful, 35 in particular when shielding effects can be tied to the orbital energy gaps Δ ε i , a = ε i – ε a in the denominator of eqn (2). We also performed the shielding analysis in terms of CMOs, but decided to forgo a discussion because the trends were less clear, mainly due to the fact that multiple occupied and unoccupied CMOs contribute to the shielding trends and no obvious relationship to the Δ ε i , a could be identified.)…”
Section: Resultsmentioning
confidence: 99%
“…The σ 11 trends are associated with the σ C1–C NLMOs, while the variations in σ 22 are associated with the σ C1–H NLMO. (Sometimes, a shielding analysis in terms of CMOs can also be very insightful, 35 in particular when shielding effects can be tied to the orbital energy gaps Δ ε i , a = ε i – ε a in the denominator of eqn (2). We also performed the shielding analysis in terms of CMOs, but decided to forgo a discussion because the trends were less clear, mainly due to the fact that multiple occupied and unoccupied CMOs contribute to the shielding trends and no obvious relationship to the Δ ε i , a could be identified.)…”
Section: Resultsmentioning
confidence: 99%
“…The contrary reality is nicely illustrated by the 13 C chemical shift of C 1 of phenyl lithium. 18 The isotropic δ value increases as C 1 becomes more negative (i.e., shielding decreases as the electron pair becomes less well bound). Each of the three principal values of the shielding tensor for C 1 changes significantly when its formal charge diminishes from 0 in benzene to −1 in phenyl lithium ( Figure 4).…”
Section: Chemical Shift and Charge Densitymentioning
confidence: 99%
“…The simulated CP-MAS 13 C spectrum of 1-13 C phenyl lithium based on the data of Berger et al18 The principal values of the shift tensor are shown (values for benzene in parentheses) with the electron orbitals, and their associated electron circulations. (See also Ref.…”
mentioning
confidence: 99%
“…This deshielding effect on the δ 13 C for the CF 3 − is counterintuitive, and explanations found in the literature are not complete. Berger et al suggested that the δ 13 C of anions may be understood using the same reason applied by the authors to explain the ipso carbon atom in phenyllithium. The ipso δ 13 C in phenyllithium is larger than in benzene due to smaller energy gap associated to C–Li bond in comparison with C–H bond.…”
Section: Introductionmentioning
confidence: 99%
“…Several works show that the δ 13 C depends on how the electronic system responds to the magnetic field; therefore, a more complex explanation is required to clarify the anion behaviour. Thus, the present study aims to demystify the deshielding effect on CF 3 − by determining the involved shielding mechanisms as well as the role of each orbital through density functional theory calculations.…”
Section: Introductionmentioning
confidence: 99%